O “novo ensino médio” no Brasil e no estado do Espírito Santo: o que nos dizem os documentos referentes acerca do desenvolvimento da cidadania e reflexão crítica - Paixão, Neusa Mara Silveira da (2023)
It intends to reflect on the counter-reformation called “New Secondary Education”, meeting the knowledge and understanding of documents that support this organization, namely: National Common Curricular Base (2018); Law No. 13,415/2017; Ordinance No. 649/2018 (Support Program for New High School); MEC Ordinance No. 1,432/2018, as well as documents from the Espírito Santo State Education Network: Implementation Plan for the New Capixaba High School (2019); the Pedagogical Guidelines for Secondary Education – Version 1.0/2021; Catalog of Deepening Training Itineraries and the textbook of the Life Project curricular component, from the state of Espírito Santo. The main objective is to investigate what the most recent official curriculum documents regarding the counter-reform of the New High School (2017/2018) express about the teaching-learning processes of Brazilian students and, in particular, of capixabas (state of Espírito Santo ), of this teaching stage, with a view to developing citizenship and critical reflection by students. It dialogues with Goodson (1995), Sacristán (2000), Silva (2003 and 2005), Libâneo (2008) and Freire (1997), regarding the concepts of curriculum and its impacts on the school routine, highlighting Covre (1991) to approach the concept of citizenship. With regard to language-related issues, it relies on studies by Mikhail Bakhtin and His Circle (2002 and 2006). It is qualitative based, with a documentary analysis. As an educational product, it highlights the production of an interactive catalog, aiming to make available and present to Basic Education teachers the most recent official curricular documents related to the High School counter-reformation, at national and state level. The text is structured in six basic chapters. In the first chapter, the academic and professional trajectory of the researcher is presented in line with the general and specific objectives. The second chapter deals with the literature review, presenting works that have already addressed this research theme or approached it. The third chapter is composed of the methodological theoretical framework, dialoguing with the authors who supported the study. Then, the fourth chapter consists of the presentation of the research methodology. The fifth chapter presents the documental analysis, through which it attempts a dialogue with documents related to the Secondary Education counter-reformation, in the sixth, it opens up to counterwords and, in the seventh, we present the educational product originated from this research, which was configured as an Interactive Catalog, entitled “Legal frameworks: what the official documents regarding the Reform of Secondary Education in Brazil and the State of Espírito Santo tell us”. The social, political and economic interests that are behind the change in the organization of the Secondary Education stage were evidenced, present in the official documents that guide the "New Secondary Education" in Brazil and in the state of Espírito Santo, as well as making it possible to question the curriculum imposed by the referred counter-reformation in the sense of its contribution to a pedagogical practice that provides the increase of citizenship and critical reflection of the students, considering that its immobilization ends up preventing the development of actions that demonstrate the participation of students in activities that allow, in a dialogic and discursive way, political and citizen participation, bringing language as the motto of the whole process.